Question #f332a

Jul 14, 2017

See a solution process below:

Explanation:

For each of these values of $x$ we need to substitute the value of $x$ for $x$ in the function and calculate the result:

• $\textcolor{red}{x} = \textcolor{red}{- 2}$

$f \left(\textcolor{red}{- 2}\right) = {3}^{\textcolor{red}{- 2}}$

$f \left(\textcolor{red}{- 2}\right) = \frac{1}{3} ^ \textcolor{red}{2}$

$f \left(\textcolor{red}{- 2}\right) = \frac{1}{9}$

• $\textcolor{red}{x} = \textcolor{red}{- 1}$

$f \left(\textcolor{red}{- 1}\right) = {3}^{\textcolor{red}{- 1}}$

$f \left(\textcolor{red}{- 1}\right) = \frac{1}{3} ^ \textcolor{red}{1}$

$f \left(\textcolor{red}{- 1}\right) = \frac{1}{3}$

• $\textcolor{red}{x} = \textcolor{red}{0}$

$f \left(\textcolor{red}{0}\right) = {3}^{\textcolor{red}{0}}$

$f \left(\textcolor{red}{0}\right) = 1$

• $\textcolor{red}{x} = \textcolor{red}{1}$

$f \left(\textcolor{red}{1}\right) = {3}^{\textcolor{red}{1}}$

$f \left(\textcolor{red}{1}\right) = 3$

Now that you know the pattern, see if you can do:

• $\textcolor{red}{x} = \textcolor{red}{2}$